The EU Model of Socially Responsible Public Procurement - Lamprinidis, Lampros (Journal of Public Policy and Administration, 2023)
Purpose: The object of this paper is an overview of the European Model of Socially Responsible Public Procurement for the purpose of knowing the civil servants involved in the public contracts and the prospective contractors about them. Public buyers spend more than 16% of the EU' GDP. By using the Public Procurement effectively by contracting authorities, one can have positive social impact (such as the reduction of criminal rate because of the employment of ex-offenders or immigrants) and contribute to sustainable development. Socially Responsible Public Procurement, in other words, take into account social considerations in public contracts in order to achieve positive social outcomes through the purchasing power of the Public Sector. Methodology: Concise review of the most important Articles of Directive 2014/24/EU related to Socially Responsible Public Procurement in the European Union will be made. Findings: Presentation of the most important articles of Directive 2014/24/EU on Socially Responsible Public Procurement Unique Contribution to Theory Practice and Policy: For the first time, stakeholders in Socially Responsible Public Procurement will have a comprehensive overview of the institutional framework in place in the European Union to be able to develop relevant public policies (employment, social policy, etc.). This work hopes to become a reference point for both Social Economy Operators and Contracting Authorities, both to facilitate the access of the former to the EU public procurement market and to provide a basis for the development of initiatives to further improve this institutional framework.